The Virtual Reality of Imprisonment: the Impact of Social Media on Prisoner Agency and Prison Structure in Russian prisons - Piacentini, Laura (Oñati Socio-Legal Series, 2018)
Prison agencies around the world are reporting a rise in the use of illicit communication devices in prison. Nevertheless, there have been no criminological studies examining prisoners’ online behavior. Using Russia as a case study, this paper reports findings from new research on prisoners’ illicit internet use and the effects on prisoner agency and prison structure. Our main finding is that Russian penality sits at the nexus of two processes. First, penality is de-institutionalised whereby the prison, discursively speaking, is no longer fixed to a built form. Second, penality is reflexively re-territorialised by placing prisoner agency onto a third space. The paper presents a new conceptual framework of prisoners as absent, which reveals Russian penality as culturally contingent and politically resilient. The interplay between de-institutionalisation and re-territorialisation has produced a new penal imaginary - a carceral motif for the twenty first century - in the form of a virtual world.